Estimasi Nilai Pasar Wajar Ekuitas PT Prima Layanan Nasional Enjiniring Dalam Persiapan Initial Public Offering (IPO) - Rizani, Ahmad (Jurnal Ekonomi Kuantitatif Terapan; 2015: Vol. 8, No. 2, Agustus 2015 (pp. 113-216)DO - 10.24843/JEKT.2015.v08.i02.p11, 2015)
PT Prima Layanan Nasional Enjiniring (PT PLN Enjiniring) plans to conduct an initial public offering in 2012 that is intended for business development. Purpose of this research was to estimate the fair market value of equity of PT PLN Enjiniring in the framework of an initial public offering. Fair market value of equity of PT PLN Enjiniring is acquired by using discounted cash flow-free cash flow to equity method. Information used for this research come from two secondary data from financial reports and other information contained in the annual report 2008-2010 PT PLN Enjiniring years audited by public accountants, comperative financial reports, and company’s stock data comparison. The estimated fair market value of equity of PT PLN Enjiniring per December 31st 2011 by using the method of discounted cash flow-free cash flow to equity is obtained indication the fair market value of equity amounting to Rp2.583.155.716.515.
Keywords: initial public offering, fair market value of equity, discounted cash flow-free cash flow to equity